Anterior and Intermediate Uveitis with Retinal Vasculitis: An Unusual Manifestation of Post-Streptococcal Uveitis Syndrome. (1st November 2016) - Filloy, Alejandro; Comas, Cristina; Català-Mora, Jaume
ABSTRACT: Purpose : To report a case of bilateral panuveitis with vasculitis, an unusual manifestation of post-streptococcal uveitis syndrome (PSU). Methods : An 8-year-old patient consulted for bilateral red eye following acute tonsillitis. Exploration revealed bilateral anterior uveitis, vitritis, macular edema, and Frosted Branch Angiitis. Given a clinical suspicion of PSU, blood and serology tests were performed to rule out other causes of vasculitis and retinitis. Results : Serologies came back negative except for highly elevated antistreptolysin-O titers. Topical and oral corticosteroids normalized the patient's visual acuity and clinical findings within a few weeks. A subsequent anterior-only recurrence was successfully resolved with topical treatment. Conclusions : Although PSU most commonly manifests as anterior uveitis, it may present with involvement of the posterior pole. To achieve a correct diagnosis, clinical suspicion and assessment of antistreptolysin-O titers as well as ruling out other conditions with similar clinical features are the mainstay approaches to diagnosis. Prognosis is generally good.